2020
DOI: 10.21043/fikrah.v8i2.8005
|View full text |Cite
|
Sign up to set email alerts
|

Kiai Sebagai Figur Toleransi Kearifan Lokal di Lasem

Abstract: <p><span>This article wants to portray the role of Kyai as inspiration for tolerance in Lasem Central Java, Indonesia. Inter-religious tolerance as Lasem peoples' local wisdom. This research focuses on a complete picture of the phenomenon being studied. The approach used is a case study by exploring community interactions in the research object. In-depth interviews were done to get the data. The result of this research shows that tolerance is an appreciation and respect between individuals or group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…So it can be concluded that spiritual values are defined to help identify a measure of a person's behavior in the search for meaning, purpose, morality, well-being about oneself, others, and reality. Kurnia Muhajarah, Belia Cahyaningrum, Rachmy Fuady Tanjung, Naily Kamaliah, Norannabiela Both when expressing spiritual values in religion, namely with God, and non-religious, concerning oneself, others, and even the universe (Izzati, 2020); ( Tanjung, Dwijayanto, Lin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So it can be concluded that spiritual values are defined to help identify a measure of a person's behavior in the search for meaning, purpose, morality, well-being about oneself, others, and reality. Kurnia Muhajarah, Belia Cahyaningrum, Rachmy Fuady Tanjung, Naily Kamaliah, Norannabiela Both when expressing spiritual values in religion, namely with God, and non-religious, concerning oneself, others, and even the universe (Izzati, 2020); ( Tanjung, Dwijayanto, Lin, 2021).…”
Section: Introductionmentioning
confidence: 99%